2021
DOI: 10.1111/bph.15581
|View full text |Cite
|
Sign up to set email alerts
|

A drug screen with approved compounds identifies amlexanox as a novel Wnt/β‐catenin activator inducing lung epithelial organoid formation

Abstract: Title: A drug screen with approved compounds identifies amlexanox as a novel Wnt/β-catenin activator inducing lung epithelial organoid formation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Distal organoid formation was done with murine lung fibroblasts (CCL206; American Type Culture Collection [ATCC]) as stromal support cells, as previously described ( Costa et al., 2021 ). Briefly, proliferation of CCL206 cells was inhibited by treatment with 10 μg/mL mitomycin C (M4287; Sigma-Aldrich) for 1 h at 37°C followed by 2 h incubation in CCL206 culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…Distal organoid formation was done with murine lung fibroblasts (CCL206; American Type Culture Collection [ATCC]) as stromal support cells, as previously described ( Costa et al., 2021 ). Briefly, proliferation of CCL206 cells was inhibited by treatment with 10 μg/mL mitomycin C (M4287; Sigma-Aldrich) for 1 h at 37°C followed by 2 h incubation in CCL206 culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…Distal progenitor cells for both the classic and 3DLD device were isolated as previously described (Jansing et al ., 2018). Distal organoid formation was performed with CCL206 cells (ATCC), murine lung fibroblasts (Mlg), as stromal support cells previously described (Costa et al, 2021). Further details for cell isolation and organoid formation, collection, fixation and imaging can be found in supplemental experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Several different in vitro and in vivo approaches have been used to identify the cell types involved in lung repair and regeneration. In vitro studies of isolated cells on tissue culture plastic or floating collagen gels were initially critical in characterizing the transition of ATII to ATI cells (Danto et al, 1995). In addition, in vivo lineage tracing has been instrumental in identifying several of the regionally specific progenitor populations (Tata and Rajagopal, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies revealed that expression of clock-pathway genes was distorted by cigarette smoke and prostaglandin I2 as well as prostacyclin were able to correct this effect and might therefore contribute to lung regeneration. Another drug-screening approach was used by C osta et al [ 100 ] with Food and Drug Administration-approved drugs using a Wnt-pathway reporter cell line, a key pathway in lung regeneration and repair. A luciferase assay in a Wnt-reporter cell line identified amlexanox as a possible Wnt-pathway activator.…”
Section: Year In Review: Preclinical Discovery and Testing Of New App...mentioning
confidence: 99%